Pengaruh Accounting Knowledge, Entrepreneurial traits, dan Subjective Norms terhadap Penggunaan Informasi Akuntansi dalam Pengambilan Keputusan Investasi UMKM di Kota Semarang - Qori Adha Fatimatus Zahro; Ratnaningrum Ratnaningrum (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
Micro, small, and medium enterprises (MSMEs) are crucial for driving regional economic expansion. Many MSMEs have not yet optimally utilized accounting data in selecting investments. This study aims to analyze the influence of accounting knowledge, entrepreneurial traits, and subjective norms on the use of accounting information in investment decision-making among MSMEs in Semarang City. Using a quantitative approach, this study surveyed 80 MSMEs selected through purposive sampling. Data were obtained through questionnaires with a five-point Likert scale and analyzed using multiple linear regression with the help of SPSS after undergoing validity, reliability, and classical assumption tests. The results showed that partially accounting knowledge (t = 3.337; sig = 0.001) and entrepreneurial traits (t = 2.272; sig = 0.026) had a positive and significant effect on the use of accounting information, while subjective norms had no significant effect (t = -0.788; sig = 0.433). Simultaneously, the three independent variables significantly influence the use of accounting information (F = 5.306; p = 0.002) with a coefficient of determination (R²) of 0.173. This finding indicates that increasing accounting and entrepreneurial knowledge can encourage the use of accounting information in investment decision-making in MSMEs.